ESTONIAN WEST COAST REVIVAL IN RETROSPECT: THE BIBLE AS A TOOL FOR INTERPRETING CHANGE = Probudžennja na zachidnomu uzberežži Estonii͏̈ v retrospektyvi: Biblija jak instrument interpretacii͏̈ pereminy - Pillii, Toivo (Bogoslovskie razmyšlenija, 2020)
The West Coast Revival in Estonia, in the 1870s and 1880s, emphasised conversion, ethical lifestyle and a joyful, experiential discipleship. This was a new, congregational paradigm that emerged in this movement, in the westernmost areas of Tsarist Russia. The Revival was deeply rooted in a fresh reading of the Bible, even if its adherents used simple and literal interpretation. Both the Moravian tradition and Swedish neopietism encouraged individual and collective hermeneutics. The Revival, being inspired by both, however, made conclusions that reached further: these awakened farmers separated from the Lutheran church, began to conduct baptism and communion independently, and discussed biblical passages between themselves in order to find guidance in the midst of religious changes. As a result,Revivalist free churches and Baptist churches were established in Estonia. The authority of the biblical texts, on which the revivalist believers built their convictions, according to their best understanding, offered new selfconfidence. Indirectly, this contributed to a strengthening of national self-awareness. The article argues that there were at least three areas where biblical interpretation helped to find guidance and convictional courage. Firstly, the Bible was used to motivate and explain independent worship, separate ecclesial patterns and maintaining a distance from the existing mainline churches, Lutheran or Orthodox. Secondly, scriptural language and images functioned both to justify and balance emotional phenomena which were characteristic of the Revival. And thirdly, biblical examples helped to interpret persecution and suffering that the revivalist believers met both from the traditional churches and from Tsarist Russian officials.